Species-specific sensitivity to PAHs reveals widespread biodiversity impact from the 2021 oil spill in the Eastern Mediterranean - Omri Lapidot; Natalie Perlin; Eli Biton; Pavel Khain; Yoav Levi; Pinhas Alpert; Debra Ramon; Nir Stern; Gil Rilov; Tamar Guy-Haim; Yoav Lehahn; Claire B. Paris; et al. (Marine Pollution Bulletin, 2026)

Paleoenvironmental constraints influencing charophyte communities in an Early Cretaceous Karstic Lake, La Pedrera de Meià Konservat-Lagerstätte (Southern Pyrenees): combining geochemical and palaeoecological analyses - Jordi Pérez-Cano; Alejandro Gil-Delgado; Oriol Oms; Ramon Mercedes-Martín (Facies, 2025)
The combined sedimentological and palaeoecological analysis of charophyte-rich carbonate microfacies is proven to be a useful methodology for the palaeoenvironmental reconstruction of continental settings. However, the integration of these charophyte assemblages with geochemical proxies has not been explored, yet. In the present work, the charophyte-rich muddy carbonates of the Barremian La Pedrera de Meià Konservat-Lagerstätte (Southern Pyrenees, Spain) were studied from a taxonomic, taphonomic, and palaeoecological viewpoint, and the results were later integrated with previously published paleoenvironmental proxies (δ 13 C, δ 18 O, and elemental geochemistry). In the studied locality, monospecific Echinochara sp.– Charaxis spicatus meadows are only found in the temporary lakes recorded in the lower stages of lake infilling. The high Al, K, Fe and Ti concentrations and δ 18 O values previously described in these carbonates indicate meteoric infilling followed by evaporation periods. Freshwater and brackish communities are found in the upper stage of lake infilling. Freshwater settings had mixed meadows with Atopochara – Clavatoraxis , Clavatoroidae utricles– Clavatoraxis , and Ascidiella – Favargerella plants, while the brackish environments, that occurred laterally to freshwater, contain meadows dominated by porocharacean– Charaxis sp., and Echinochara sp. –Charaxis spicatus plants. Miliolids and broken dasycladaceans also occur in these facies. Sr/Ba ratios, REE + Y concentrations, and δ 18 O values previously reported in these lacustrine carbonates indicate prevalence of freshwater environments with occasional marine influence, which agrees with the occurrence of distinct brackish and freshwater charophyte assemblage and marine-affinity organisms, suggesting that during the last stage of lake evolution, the system was part of a coastal wetland. This work demonstrates that the integration of geochemical, palaeontological and palaeoecological datasets improves the understanding of the fossil continental carbonate settings and their evolution.

Geochemical approach for decoding the paleoenvironmental and depositional evolution of a coastal lacustrine Konservat-Lagerstätte (Early Cretaceous, south-Central Pyrenees) - Alejandro Gil-Delgado; David Cruset; Oriol Oms; Edgar Botero; Jordi Ibáñez-Insa; Xavier Delclòs; Albert Sellés; Àngel Galobart; Ramon Mercedes-Martín (Sedimentary Geology, 2023)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Arginine deiminase pathway genes and arginine degradation variability in Oenococcus oeni strains - Isabel Araque; Joana Gil; Ramon Carreté; Magda Constantí; Albert Bordons; Cristina Reguant (Folia Microbiologica, 2016)

Nidogen 1 and Nuclear Protein 1: novel targets of ETV5 transcription factor involved in endometrial cancer invasion - Núria Pedrola; Laura Devis; Marta Llauradó; Irene Campoy; Elena Martinez-Garcia; Marta Garcia; Laura Muinelo-Romay; Lorena Alonso-Alconada; Miguel Abal; Francesc Alameda; Gemma Mancebo; Ramon Carreras; et al. (Clinical & Experimental Metastasis, 2015)

Influence of tillage on soil macropore size, shape of top layer and crop development in a sub-humid environment - Ramon Josa; Gil Gorchs; Marta Ginovart; Albert Solé-Benet (Biologia, 2013)

Generation and characterization of orthotopic murine models for endometrial cancer - Silvia Cabrera; Marta Llauradó; Josep Castellví; Yolanda Fernandez; Francesc Alameda; Eva Colás; Anna Ruiz; Andreas Doll; Simó Schwartz; Ramon Carreras; Jordi Xercavins; Miguel Abal; et al. (Clinical & Experimental Metastasis, 2012)

Effect of the presence of the plant growth promoting rhizobacterium (PGPR) Chryseobacterium balustinum Aur9 and salt stress in the pattern of flavonoids exuded by soybean roots - Marta S. Dardanelli; Hamid Manyani; Sergio González-Barroso; Miguel A. Rodríguez-Carvajal; Antonio M. Gil-Serrano; Maria R. Espuny; Francisco Javier López-Baena; Ramon A. Bellogín; Manuel Megías; Francisco J. Ollero (Plant and Soil, 2010)

Molecular diversity among marine picophytoplankton as revealed by psbA analyses - Gil Zeidner; Christina M. Preston; Edward F. Delong; Ramon Massana; Anton F. Post; David J. Scanlan; Oded Béjà (Environmental Microbiology, 2003)
Summary Photosynthetic microorganisms play a crucial role in the marine environment. In vast areas of the oceans, marine primary productivity is performed by cells smaller than 2–3 µm (picoplankton). Here, we report on molecular analyses of the conserved photosynthetic psbA gene (coding for protein D1 of photosystem II reaction centre) as a diversity indicator of naturally occurring marine oxygenic picophytoplankton. The psbA genes proved to be good indicators of the presence of a wide variety of photosynthetic marine microbial groups, including new cyanobacterial groups and eukaryotic algae (prasinophytes). Furthermore, using environmental bacterial artificial chromosome (BAC) libraries, we were able to correlate psbA genes with small subunit rRNAs and, therefore, to confirm their phylogenetic affiliation.

Association of protein kinase CK2 with eukaryotic translation initiation factor eIF-2 and with grp94/endoplasmin - Marta Riera; Nerea Roher; Francesc Miró; Carles Gil; Ramon Trujillo; José Aguilera; Maria Plana; Emilio Itarte (Molecular and Cellular Biochemistry, 1999)

Heritability of running economy: a study made on twin brothers - Gil Rodas; Mar Calvo; Asuncin Estruch; Eduardo Garrido; Guadalupe Ercilla; Antoni Arcas; Ramon Segura; Josep L. Ventura (European Journal of Applied Physiology, 1998)

Diversity and status of sea turtle species in the Gulf of Guinea islands - Javier Castroviejo; Javier Juste B; Jaime Del Val Pérez; Ramon Castelo; Ramon Gil (Biodiversity and Conservation, 1994)